The Influence of Brand Experience on Brand Loyalty through Perceived Quality, Brand Trust and Customer Satisfaction as Mediation - Wahyuddin M Rahmat; Kurniawati Kurniawati (SEIKO : Journal of Management & Business, 2022)
Abstract The purpose of this study is to determine the influence of brand experience on brand loyalty by adding perceived quality, brand trust and customer satisfaction as mediating variables. The collection method in this study was by non-probability sampling method and purposive sampling technique. The data used in this study are quantitative data obtained from a questionnaire with a total of 306 respondents. With a 5-point Likert Scale it ranges from 1 (Strongly Disagree) to 5 (Strongly Agree). The results of the study revealed that there is a positive relationship between Brand Experience to Perceived Quality, Brand Experience to Customer satisfaction, Brand Experience to Brand Trus, Brand Experience to Brand Loyalty and Brand Trust to Brand Loyalty. The managerial implication in this study is that the shoe rodusen is to add innovation as an example, namely adding the latest model model that suits the interests of the market or consumers, so that consumers will be interested in buying shoe products produced by manufacturers. In addition, manufacturers must conduct more surveys about what the market wants, while also being actively involved in social media in order to survive in the manufacturing and fashion industries because market interest is also influenced, one of which is by technological advances and social media. Keywords: Brand Experience, Brand Loyalty, Perceived Quality, Brand Trust, Customer Satisfaction. Abstrak Penelitian ini bertujuan guna mengetahui pengaruh pengalaman merek terhadap loyalitas merek dengan menambahkan kualitas yang dirasakan, kepercayaan merek dan kepuasan pelanggan sebagai variable mediasi. Metode pengumpulan pada penelitian ini dengan metode non-probability sampling dan teknik purposive sampling. Data yang dipakai pada penelitian ini ialah data kuantitatif yang didapatkan dari kuesioner dengan jumlah responden 306 responden. Dengan Skala Likert 5 poin berkisar dari 1 (Sangat Tidak Setuju) hingga 5 (Sangat Setuju). Hasil penelitian mengungkapkan bahwa adanya hubungan positif antara Brand Experience terhadap Perceived Quality, Brand Experience terhadap Costumer satisfaction, Brand Experience terhadap Brand trus, Brand Experience terhadap Brand Loyalty dan Brand Trust terhadap Brand Loyalty. Implikasi manajerial dalam penelitian ini yaitu produsen sepatu adalah untuk menambah melakukan inovasi sebagai contoh yakni menambahkan model model yang terbaru yang sesuai dengan minat pasar ataupun konsumen,sehingga konsumen akan tertarik untuk membeli produk sepatu yang dihasilkan oleh produsen. Selain itu produsen harus lebih banyak melakukan survey tentang apa yang diinginkan pasar selain itu juga terlibat aktif di media sosial agar tetap bisa bertahan di industri manufaktur dan fashion karena minat pasar juga dipengaruhi salah satunya oleh kemajuan teknologi dan sosial media. Kata Kunci : Brand Experience, Brand Loyalty, Perceived Quality, Brand Trust, Customer Satisfaction.